The immunomodulatory impact of naturally derived neem leaf glycoprotein on the initiation progression model of 4NQO induced murine oral carcinogenesis: a preclinical study - Juhina Das; Saurav Bera; Nilanjan Ganguly; Ipsita Guha; Tithi Ghosh Halder; Avishek Bhuniya; Partha Nandi; Mohona Chakravarti; Sukanya Dhar; Anirban Sarkar; Tapasi Das; Saptak Banerjee; et al. (Frontiers in Immunology)
IntroductionMurine tumor growth restriction by neem leaf glycoprotein (NLGP) was established in various transplanted models of murine sarcoma, melanoma and carcinoma. However, the role of NLGP in the sequential carcinogenic steps has not been explored. Thus, tongue carcinogenesis in Swiss mice was induced by 4-nitroquinoline-1-oxide (4NQO), which has close resemblance to human carcinogenesis process. Interventional role of NLGP in initiation-promotion protocol established during 4NQO mediated tongue carcinogenesis in relation to systemic immune alteration and epithelial-mesenchymal transition (EMT) is investigated.Methods4NQO was painted on tongue of Swiss mice every third day at a dose of 25µl of 5mg/ml stock solution. After three consecutive treatments with 4NQO (starting Day7), one group of mice was treated with NLGP (s.c. 25μg/mice/week), keeping a group as PBS control. Mice were sacrificed in different time-intervals to harvest tongues and studied using histology, immunohistochemistry, flow-cytometry and RT-PCR on different immune cells and EMT markers (e-cadherin, vimentin) to elucidate their phenotypic and secretory status.ResultsLocal administration of 4NQO for consecutive 300 days promotes significant alteration in tongue mucosa including erosion in papillae and migration of malignant epithelial cells to the underlying connective tissue stroma with the formation of cell nests (exophytic-hyperkeratosis with mild dysplasia). Therapeutic NLGP treatment delayed pre-neoplastic changes promoting normalization of mucosa by maintaining normal structure. Flow-cytometric evidences suggest that NLGP treatment upregulated CD8+, IFNγ+, granzyme B+, CD11c+ cells in comparison to 4NQO treated mice with a decrease in Ki67+ and CD4+FoxP3+ cells in NLGP treated cohort. RT-PCR demonstrated a marked reduction of MMP9, IL-6, IL-2, CD31 and an upregulation in CCR5 in tongues from 4NQO+NLGP treated mice in comparison to 4NQO treated group. Moreover, 4NQO mediated changes were associated with reduction of e-cadherin and simultaneous up-regulation of vimentin expression in epithelium that was partially reversed by NLGP.DiscussionEfficacy of NLGP was tested first time in sequential carcinogenesis model and proved effective in delaying the initial progression. NLGP normalizes type 1 immunity including activation of the CD8+T effector functions, reduction of regulatory T cell functions, along with changes in EMT to make the host systemically alert to combat the carcinogenic threat.